Effects of knowledge management on client-vendor relationship quality: the mediating role of global mindset. Issue 6 (10th October 2016) - Sharma, Revti Raman; Chadee, Doren; Roxas, Banjo
Abstract : Purpose: This study argues that knowledge management (KM) by itself has only limited effects on client–vendor relationship (CVR) of global providers of highly customised services. Rather, it is the ability of top management to properly evaluate and utilise a vast array of complex knowledge which allows global firms to develop and maintain superior CVR. The paper tests the proposition that global mindset (GM) of top management mediates the effects of KM on CVR quality. Design/methodology/approach: The paper uses survey data from a sample of 68 international service providers (ISPs) in the information technology sector in India and partial least squares approach to structural equation modelling to test the hypotheses. Findings: The results show that both KM and GM have positive and statistically significant effects on the quality of CVRs. The results also confirm that the GM of top management has significant and substantive mediation effects on the relationship between KM and CVR quality. Research limitations/implications: The small size of the sample and the focus on ISPs in a single country constitute the main limitations of the study. Future research should ideally draw from a larger sample of ISPs from multiple countries and sectors in order to allow for greater generalisation of the findings. Practical implications: ISPs will benefit from developing the GM of their top management teams to enhance their CVRs. Originality/value: The paper provides new insights into how, in an international context, firms can transform their KM into superior CVR quality through the development of GM.